Cardiovascular implantable electronic device therapy in patients with left ventricular assist devices: insights from TRAViATA. (1st October 2021) - Darden, Douglas; Ammirati, Enrico; Brambatti, Michela; Lin, Andrew; Hsu, Jonathan C.; Shah, Palak; Perna, Enrico; Cikes, Maja; Gjesdal, Grunde; Potena, Luciano; Masetti, Marco; Jakus, Nina; et al.
Abstract: Background: There is conflicting observational data on the survival benefit cardiac implantable electronic devices (CIED) in patients with LVADs. Methods: Patients in whom an LVAD was implanted between January 2008 and April 2017 in the multinational Trans-Atlantic Registry on VAD and Transplant (TRAViATA) registry were separated into four groups based on the presence of CIED prior to LVAD implantation: none ( n = 146), implantable cardiac defibrillator (ICD) ( n = 239), cardiac resynchronization without defibrillator (CRT-P) ( n = 28), and CRT with defibrillator (CRT-D) ( n = 111). Results: A total of 524 patients (age 52 years ±12, 84.4% male) were followed for 354 (interquartile range: 166–701) days. After multivariable adjustment, there were no differences in survival across the groups. In comparison to no device, only CRT-D was associated with late right ventricular failure (RVF) (hazard ratio 2.85, 95% confidence interval [CI] 1.42–5.72, p = 0.003). There was no difference in risk of early RVF across the groups or risk of ICD shocks between those with ICD and CRT-D. Conclusion: In a multinational registry of patients with LVADs, there were no differences in survival with respect to CIED subtype. However, patients with a pre-existing CRT-D had a higher likelihood of late RVF suggesting significant long-term morbidity in those with devices capable of LV‑lead pacing post LVAD implantation. Highlights: In a multinational registry of patients with continuous flow LVAD, there were no differences in survival with respect to type of CIED . Those with CRT-D were at nearly threefold higher risk of late right ventricular heart failure as compared to no device. There was no difference in the risk of defibrillator shocks between those with an ICD only and CRT-D. Randomized clinical trials are needed to evaluate the benefit as well as the hemodynamic and arrhythmogenic risk of CIED in those with a LVAD.